Vitamin D levels in pregnant women in southern Brazil during Summer and Winter - Rahal Chrisostomo, Kadija (2022)
Objective: To evaluate serum vitamin D levels and respective seasonality in pregnant women in southern Brazil. Methods: This was an analytical prospective cross-sectional study set at prenatal outpatient clinics of two public teaching hospitals. A total of 520 pregnant women were included, 256 in the Summer and 264 in the Winter of 2016. Women were divided into a high-risk group of patients with preeclampsia, gestational diabetes mellitus, or human immunodeficiency virus seropositivity, and a low-risk group of disease-free patients. Sociodemographic, epidemiologic, and clinical data were collected, and blood was sampled for assessment of vitamin D levels. Serum 25 hydroxyvitamin D levels were measured by chemiluminescence. Results: The mean serum vitamin D levels were 22.5 ± 8.70 ng/mL in the high-risk group and 56.2 ± 21.75 nmol/L in the low-risk group, with significantly higher levels in Summer (26.7 ± 7.80 ng/mL and 66.7 ± 19.50 nmol/L, respectively) compared with Winter (18.3 ± 7.50 ng/mL and 45.7 ± 18.75 nmol/L, respectively; p <0.001). The prevalence of hypovitaminosis D was 69.9% in Summer and 91.3% in Winter (p <0.001). Both groups had a significantly higher prevalence of hypovitaminosis D in Winter compared to Summer (high-risk group, 92.4% vs. 71.2%, p <0.001; low-risk group, 87.0% vs. 64.7 p <0.011%). Conclusion: A high prevalence of hypovitaminosis D was found in this cohort of pregnant women, particularly during Winter, raising awareness of the need to recommend adequate nutrition through a healthy and balanced diet and adequate sun exposure in prenatal care.